Dry Eye Disease Association with Computer Exposure Time Among Subjects with Computer Vision Syndrome - Sánchez-Valerio MR (Dove Medical Press, 2020)
María del Rosario Sánchez-Valerio,1 Karim Mohamed-Noriega,2 Irma Zamora-Ginez,1 Blanca Guadalupe Baez Duarte,1 Verónica Vallejo-Ruiz3 1Faculty of Medicine, Autonomous University of Puebla, Puebla, Puebla, México; 2Autonomous University of Nuevo León (UANL), Faculty of Medicine, University Hospital “José E. Gonzalez, Ophthalmology Department, Monterrey, México; 3Eastern Biomedical Research Center, Mexican Social Security Institute (IMSS), Metepec, Puebla, MéxicoCorrespondence: María del Rosario Sánchez-Valerio Tel +52 22 26039032Email rosyoft_@hotmail.comPurpose: To assess the time of exposure to the computer and dry eye disease (DED) in subjects with computer vision syndrome (CVS).Methods: A cross-sectional study was conducted in office workers, computer users of both sexes, with an age range of 18– 45 years without comorbidities; we included 108 subjects divided into 3 groups according to the time of computer exposure in hours per day (H/D): < 4 (n = 23), 4 − 7.9 (n = 49), > 8 (n = 39). A specific questionnaire was applied to them on the exposure time and the type of visual display terminal (VDT) used, as well as the computer vision symptoms scale (CVSS17). DED was diagnosed with the Ocular Surface Disease Index (OSDI). Ocular surface damage and signs of DED were evaluated with the tear rupture time test (TBUT), the integrity of the ocular surface by ocular surface staining (OSS) and the production of the aqueous basal tear film using the Schirmer test.Results: Average computer exposure time, measured differently, was positively correlated with DED development. The computer exposure time measured in hours per year and TBUT showed a significant negative correlation (p < 0.001) (rho − 0.463). Years of computer exposure and staining of the ocular surface showed a significant positive correlation (p < 0 0.001; rho 0.404). The accumulated exposure time was negatively correlated with TBUT (p < 0.001; rho − 0.376) and positively with OSS (p < 0.001; rho 0.433). Schirmer test did not correlate with computer exposure time.Conclusion: The prolonged time of exposure to the computer in subjects with CVS was significantly correlated with the DED tests, in the different ways of measuring it; but not with the Schirmer test.Keywords: computer vision syndrome, dry eye disease.